When Home Is Still Unsafe: From Family Reunification to Foster Care Reentry. Issue 5 (18th May 2018) - Font, Sarah A.; Sattler, Kierra M. P.; Gershoff, Elizabeth
Abstract : Reuniting children with their families is the preferred outcome of foster care, yet many children reunited with their families reenter foster care. This study examined how parental substance abuse and mental health problems, and the time allotted for reunification, are associated with reentry risk. We used a complete cohort of children who entered the Texas foster care system in fiscal years 2008 and 2009 to identify the risk of foster care reentry within 5 years of reunification using selection‐adjusted multilevel survival analysis. Approximately 16% of reunified children reentered care within 5 years. Substance abuse and mental health problems predicted higher rates of reentry. Reunification after 12 months was associated with increased reentry risk overall, but not among children commonly exempted from federal permanency timelines. Permanency guidelines that restrict the length of time to achieve reunification may have the unintended consequence of pushing reunification before maltreatment risks have been resolved.